Tools for Stools – Recognising and Managing Constipation on an Older Adult Inpatient Ward: A Quality Improvement Project - Aishwarya Nathan; Romesa Khan; Modupe Odumosu; Louisa Bird; Margaret Ogbeide-Ihama (BJPsych Open)
Aims: Constipation is a common problem in psychiatric patients and can have serious consequences. Patients taking antipsychotics with anticholinergic properties are at higher risk of constipation. The risk is further increased in older adults due to reduced mobility and polypharmacy. To treat constipation, patients should have their bowel movements monitored and preventative laxatives considered. We faced similar challenges and this project was undertaken following a Serious Untoward Incident due to constipation related complications,